2015
DOI: 10.1007/s11060-014-1695-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the peritumoral brain zone in glioblastoma: a multidisciplinary analysis

Abstract: Glioblastoma (GB) is the most frequent and aggressive type of primary brain tumor. Recurrences are mostly located at the margin of the resection cavity in the peritumoral brain zone (PBZ). Although it is widely believed that infiltrative tumor cells in this zone are responsible for GB recurrence, few studies have examined this zone. In this study, we analyzed PBZ left after surgery with a variety of techniques including radiology, histopathology, flow cytometry, genomic, transcriptomic, proteomic, and primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…Multiple studies 4,5,6 have demonstrated that GBM heterogeneity is not limited to the tumour margins but also involves the peritumoral brain parenchymal zone (PBZ), with roughly 90% of GBM recurrences occurring in the PBZ. 7 Few studies 8 have investigated the PBZ and its microenvironment suggesting that interaction of specific cells (i.e. glioma cells, vascular endothelial, neuroglial, and microglial cells 9,10 ) and molecular events in PBZ contribute to tumour infiltration, blood brain barrier compromise, and micro vascularity, ultimately leading to poor survival in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies 4,5,6 have demonstrated that GBM heterogeneity is not limited to the tumour margins but also involves the peritumoral brain parenchymal zone (PBZ), with roughly 90% of GBM recurrences occurring in the PBZ. 7 Few studies 8 have investigated the PBZ and its microenvironment suggesting that interaction of specific cells (i.e. glioma cells, vascular endothelial, neuroglial, and microglial cells 9,10 ) and molecular events in PBZ contribute to tumour infiltration, blood brain barrier compromise, and micro vascularity, ultimately leading to poor survival in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…If radical resection is impossible due to tumor location near eloquent regions of the brain, the aim is maximal tumor resection with preservation of brain function. The extent of resection influences the prognosis, and it is known that malignant gliomas extend beyond their contrast-enhancing border with a diffuse, non-enhancing infiltration into the peritumoral edema, which complicates the assessment of the remaining tumor burden [18,19]. These diffuse, non-enhancing tissue changes are not easily detected visually on conventional MR images, but can to some extent be identified with diffusion and perfusion imaging, which correlates with histopathological features of the tumors [20].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, this area shows hyper-intensity on T 2 WI and FLAIR images due to vasogenic edema [40]; as the blood-brain barrier breaks down, capillary permeability increases, a pressure gradient from the vasculature to the extracellular environment is formed, and many intravascular proteins penetrate into the extra-cellular space [41]. In this study, the APTw value in the PBZ of SBMs and GBMs was significantly higher than in the CNAWM ( P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In metastases brain tumors, PBZ T 2 hyperintensity mainly reflects vasogenic edema [7; 35]. In the GBMs, it is hypothesized that specific cells and inflammatory cells infiltrate into the PBZ [40; 4244], and that the PBZ T 2 hyperintensity reflects more than vasogenic edema. Technically, the APTw effect is due to the shift of amide proton from mobile proteins and peptides to water proton [12].…”
Section: Discussionmentioning
confidence: 99%